Balkan Countries and Democracy Index (2017) - Blagoeva, Blaga (Research Papers, 2019)
The paper analyses the results from the Economist Intelligence Unit’s research for Democracy Index 2017. It starts by offering a general presentation of the research and focuses specifically on the results of Bulgaria and other Balkan countries on several major criteria: Electoral process and pluralism; Functioning of government; Political participation; Political culture; Civil liberties. The paper seeks to answer the question why there aren’t “Full Democracies” in the Balkans?
Keywords: Balkans; Democracy index; Bulgaria